The nonlinear analysis of the reproductive system model - Švitra, Donatas; Grigolienė, Rasa (Lietuvos matematikos rinkinys, 1998)
There are presented the female reproductive system mathematical model. We may interpret relations of the analysed system as the ecological problem "a predator—victim". It is presented the nonlinear analysis of the model in this work. At help the PC and using Euler's counting method, we find the solutions of system and compare the received results with the experimental data.